Oxidative metabolism deficiencies in brains of patients with Alzheimer's disease - Hoyer, Siegfried (Acta neurologica Scandinavica, 1996)
Glucose metabolism in the brain has an important influence on many normal cellular processes. It contributes to the synthesis of acetylcholine, glutamate, aspartate, γ-aminobutyric acid, glycine, and ATP production (the driving force behind almost all cellular and molecular activity). Neuronal glucose metabolism is controlled antagonistically by insulin and cortisol. Desensitization of the neuronal insulin receptor causes abnormalities in oxidative energy metabolism. During normal aging, the cerebral energy pool is slightly diminished, but its level increases after stressful events. In age-related sporadic late-onset dementia of the Alzheimer type (SDAT), glucose metabolism and formation of cellular energy are severely reduced. Desensitization of the neuronal insulin receptor seems to be an early event in the pathogenesis or even etiology of SDAT causing disturbances in oxidative glucose metabolism and energy failure in insulin-sensitive brain structures. These abnormalities appear to induce a cascade of disturbances that leads to abnormal APP processing and amyloid formation, membrane damage, and neuronal death.